The Philosophy of Desire in the Buddhist Pali Canon - Webster, David (Routledge Critical Studies in Buddhism, 2005)
David Webster explores the notion of desire as found in the Buddhist Pali Canon. Beginning by addressing the idea of a 'paradox of desire', whereby we must desire to end desire, the varieties of desire that are articulated in the Pali texts are examined. A range of views of desire, as found in Western thought, are presented as well as Hindu and Jain approaches. An exploration of the concept of ditthi(view or opinion) is also provided, exploring the way in which 'holding views' can be seen as analogous to the process of desiring. Other subjects investigated include the mind-body relationship, the range of Pali terms for desire, and desire's positive spiritual value. A comparative exploration of the various approaches completes the work.